Theoretical elasticity - Green, A. E. 1912-1999; Zerna, Wolfgang 1916-2005 (Clarendon Press, 1975)
This highly regarded engineering manual is mainly concerned with three important aspects of elasticity theory: finite elastic deformations, complex variable methods for two-dimensional problems for both isotropic and aeolotropic bodies, and shell theory. Also discussed are three-dimensional problems for isotropic and transversely isotropic bodies. (MOD).
Keywords: Elastizitätstheorie; Elastizität